RESPONSES TO DIGITAL HUMAN RESOURCE MANAGEMENT MODEL: SUGGESTIONS FROM DISRUPTIVE INNOVATION THEORY - Vu, Thi Thuy (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2024)
Purpose – Considering the popularity of digital technologies, the study aims to provide additional perspective of why managers have low commitment to digital human resource management (HRM) model and how they should interpret and respond to this model. Body of knowledge – The study indicates that rushing to adopt digital HRM model is not encouraged, even though the model has potential benefits in terms of organizational efficiency and employee experience. However, the ignorance of its usage possibilities can make HR managers and professionals lose their control over HR activities to other business units. Implications – Managers need to understand the driving factors of digital HRM model, do critical analysis of its relation to the current business model, and evaluate potential impacts of its adoption on the organization. Based on these analyses, managers can establish a suitable response plan to the disruption, which can range from ignorance at the first time to full integration in the long run. Originality/Value – The emergence of digital technologies have disrupted the way organization operate their internal business processes. Compared to other functions, human resource management is likely to be overlooked in organization’s digital transformation plan, even though human resource is considered to be an important resource for its competitive advantages in today’s uncertain and fast changing world. The study contributes to drawing additional attention to the importance of digital HRM in organization’s digital transformation plan and provides additional perspective to interpret and implement digital HRM.